Identification of diverse RNA viruses in Obscuromonas flagellates (Euglenozoa: Trypanosomatidae: Blastocrithidiinae) - Grybchuk, Danyil; Galan, Arnau; Klocek, Donnamae; Macedo, Diego H; Wolf, Yuri I; Votýpka, Jan; Butenko, Anzhelika; Lukeš, Julius; Neri, Uri; Záhonová, Kristína; Kostygov, Alexei Yu; Koonin, Eugene V; et al. (Virus evolution, 2024)
Trypanosomatids (Euglenozoa) are a diverse group of unicellular flagellates predominately infecting insects (monoxenous species) or circulating between insects and vertebrates or plants (dixenous species). Monoxenous trypanosomatids harbor a wide range of RNA viruses belonging to the families Narnaviridae, Totiviridae, Qinviridae, Leishbuviridae, and a putative group of tombus-like viruses. Here, we focus on the subfamily Blastocrithidiinae, a previously unexplored divergent group of monoxenous trypanosomatids comprising two related genera: Obscuromonas and Blastocrithidia. Members of the genus Blastocrithidia employ a unique genetic code, in which all three stop codons are repurposed to encode amino acids, with TAA also used to terminate translation. Obscuromonas isolates studied here bear viruses of three families: Narnaviridae, Qinviridae, and Mitoviridae. The latter viral group is documented in trypanosomatid flagellates for the first time. While other known mitoviruses replicate in the mitochondria, those of trypanosomatids appear to reside in the cytoplasm. Although no RNA viruses were detected in Blastocrithidia spp., we identified an endogenous viral element in the genome of B. triatomae indicating its past encounter(s) with tombus-like viruses.
Keywords: Qin-like virus; Mitoviridae; Obscuromonas; Narnaviridae; Blastocrithidia; dsRNA viruses